Դիտարկումներ գուսան եզրույթի փոխակերպության վերաբերյալ - Պետրոսյան, Սահակ («Զանգակ - 97»)
Gusan concept by its literary significance has wide diversity and has Parthian roots (gosana).Gusan term includes Community of wandering. strolling and vagant musicians, rhapsodes and others. The institute of gusans has a significant place in Aimenian and Iranian ethnic - cultural world and in the course of time it was developing and enriching by new views and reflections of life. Medieval Armenian gusans' creative and luxuriant imagination is exceptionally capacious and versatile. They reflected heroic myths of current emperors courage and social-historical events.
Keywords: Լեզվաբանություն; Բանահյուսություն